#### Answer

$\dfrac {1}{2}$

#### Work Step by Step

$2^{6-3x}=8^{x+1}\Rightarrow 2^{6-3x}=\left( 2^{3}\right) ^{x+1}\Rightarrow 2^{6-3x}=2^{3x+3}\Rightarrow 6-3x=3x+3\Rightarrow 6x=3\Rightarrow x=\dfrac {1}{2}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$\dfrac {1}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.